$C^*$-algebras of labelled graphs II - simplicity results - Bates, Teresa; Pask, David (MATHEMATICA SCANDINAVICA, 2009)
We prove simplicity and pure infiniteness results for a certain class of labelled graph $C^*$-algebras. We show, by example, that this class of unital labelled graph $C^*$-algebras is strictly larger than the class of unital graph $C^*$-algebras.